Development and internal validation of the patient safety experience scale for inpatients - On-Jeon Baek; Sun-Hwa Shin (PLoS ONE, 2025)
There is an increasing need for a practical instrument that captures patient safety experiences from the inpatient perspective and is suitable for clinical application. This study aimed to develop a Patient Safety Experience Scale (PSES) reflecting inpatient safety indicators and to evaluate its reliability and validity. An initial pool of 90 items was generated through a literature review and qualitative interviews, from which 60 items were selected based on expert evaluation and content validity assessment. A survey was conducted among 549 inpatients. Data were analyzed using item analysis, confirmatory factor analysis, Pearson’s correlation, Cronbach’s alpha, and intraclass correlation coefficients (ICC) using SPSS 26.0 and AMOS 21.0. The final scale comprised 30 items across six factors: patient identification, prevention of medication errors, fall prevention, infection prevention, compliance with safety in daily life, and information sharing. The PSES demonstrated excellent internal consistency (Cronbach’s α = .95) and strong test–retest reliability (ICC = .89). Additionally, it showed strong concurrent validity with the patient participation scale, with a correlation coefficient of.91. These findings support the internal validity of the PSES as a reliable and feasible instrument for systematically assessing safety experiences of inpatients. This scale may facilitate targeted quality improvement efforts and contribute to fostering a patient-centered safety culture in healthcare settings.